Karakteristik Geokimia Basal Alkali Formasi Manamas di Sungai Bihati, Baun, Pulau Timor - Widiatama, Angga Jati; Santy, Lauti Dwita; Natalia, Happy Christin; Wahyudiono, Joko; Ikhram, Rinaldi (EKSPLORIUM, 2021)
The igneous rock of Manamas Formation in the Bihati River, Baun is one of the igneous rock outcrops in Timor Island that has not been widely studied based on its geochemical characteristic. This study aims to determine the genesis and processes that occur in the igneous rocks of the Manamas Formation within tectonic framework of Timor Island based on petrographic and geochemical analysis. X-ray Fluorescence (XRF) and Inductively Coupled Plasma-mass Spectrometery (ICP-MS) were used to determine the major elements, trace elements, and rare earth elements. The igneous rock of the Manamas Formation is a basalt intrusion with an alkaline affinity which shown an enrichment pattern of rare earth elements identical to Ocean Island Basalt (OIB). This study proves the existence of two different mechanisms of elemental enrichment, fluid related enrichment which related to the subduction activity of the Indian Ocean plate under the Banda Arc and also melt related enrichment which originated from the broken Indian Ocean plate which enters the OIB reservoir zone. The two different magmas then mix and underplating beneath the Banda Arc.